2012
DOI: 10.1021/bi300070z
|View full text |Cite
|
Sign up to set email alerts
|

P3–P3′ Residues Flanking Scissile Bonds in Factor VIII Modulate Rates of Substrate Cleavage and Procofactor Activation by Thrombin

Abstract: Thrombin-catalyzed activation of factor VIII (FVIII) occurs through proteolysis at three P1 Arg residues: Arg372 and Arg740 in the FVIII heavy chain and Arg1689 in the FVIII light chain. Cleavage at the latter two sites is relatively fast compared with cleavage at Arg372, which appears to be rate-limiting. Examination of the P3–P3′ residues flanking each P1 site revealed that those sequences at Arg740 and Arg1689 are more optimal for thrombin cleavage than at Arg372, suggesting these sequences may impact react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Instead, it is likely that the extra occluding region including the Arg-566 residue which notably protrudes into the catalytic cavity functions in substrate selection by ASP, as seen in that by Kex2. In addition, in the thrombin-catalyzed activation of factor VIII, it was reported that P3-P3' residues flanking scissile bonds in the factor VIII modulate substrate was cleaved by thrombin [25]. This report may be another example indicating that the amino acid residues adjacent to the cleavage site of a substrate largely affect the proteolytic action.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it is likely that the extra occluding region including the Arg-566 residue which notably protrudes into the catalytic cavity functions in substrate selection by ASP, as seen in that by Kex2. In addition, in the thrombin-catalyzed activation of factor VIII, it was reported that P3-P3' residues flanking scissile bonds in the factor VIII modulate substrate was cleaved by thrombin [25]. This report may be another example indicating that the amino acid residues adjacent to the cleavage site of a substrate largely affect the proteolytic action.…”
Section: Resultsmentioning
confidence: 99%
“…During activation, thrombin cleaves FVIII after Arg372 (A1-A2 junction), Arg740 (A2-B junction), and Arg1689 (N-terminal region of A3 domain), which results in the formation of an FVIIIa heterotrimer A1/A2/A3-C1-C2 [ 9 ]. The initial cleavage site is after Arg740, which subsequently facilitates the cleavage at the other two positions [ 11 ], while cleavage after Arg372 is the rate-limiting step of FVIII activation [ 12 , 13 ]. Besides FVIII, thrombin activates other components of the blood coagulation cascade and is involved in fibrinolysis [ 14 , 15 ], inflammation, atherosclerosis [ 16 , 17 ], and neurodegeneration [ 18 , 19 ], where it has numerous protein substrates [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct P1-S1 interactions of the substrate with this amino acid explain the strong preference of thrombin for positively charged substrate residues (especially arginine residues) at P1 (C-terminal to the scissile bond). Further requirements have also been described for flanking amino acids [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%